2021
DOI: 10.1002/adma.202004172
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Materials for Modulation of Macrophage Fate

Abstract: Human immune system acts as a pivotal role in the tissue homeostasis and disease progression. Immunomodulatory biomaterials that can manipulate innate immunity and adaptive immunity hold great promise for a broad range of prophylactic and therapeutic purposes. This review is focused on the design strategies and principles of immunomodulatory biomaterials from the standpoint of materials science to regulate macrophage fate, such as activation, polarization, adhesion, migration, proliferation, and secretion. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 409 publications
(438 reference statements)
2
136
0
Order By: Relevance
“…[ 6,7 ] These prior studies suggest that materials designed to carry physical screens with their gaps to bioactive material surface are tunable and can both modulate and elucidate delicate cell–ECM interactions. [ 8–13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,7 ] These prior studies suggest that materials designed to carry physical screens with their gaps to bioactive material surface are tunable and can both modulate and elucidate delicate cell–ECM interactions. [ 8–13 ]…”
Section: Introductionmentioning
confidence: 99%
“…M1 macrophages play important roles in in ammation by secreting pro-in ammatory mediators, including IL-1, IL-6, TNF-α, and IL-12. In contrast, M2 macrophages are characterised by the secretion of high levels of anti-in ammatory mediators, such as IL-10 and TGF-β [25][26][27]. In the present study, we found that macrophages, which partly govern tissue regeneration, showed different polarization patterns after translation of MSCs from different sources.…”
Section: Discussionmentioning
confidence: 50%
“…It is well established that M2 macrophages help to inhibit inflammation and promote tissue regeneration, whereas M1 macrophages have the opposite effects. [ 16 ] Therefore, the cell composition in the defect areas was analyzed to explore the possible explanation for the chirality‐dependent variation in inflammation and regeneration. At day 3, the number of macrophages with the M2 surface marker CD206 was higher in the M group than in the P group, whereas the proportion of macrophages with the M1 surface marker CCR7 in both groups was similar (Figure 2d and Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%